Relatório de Estágio Profissional "Aprender a (o) Ensinar - Tiffany Costa Poças (2017)
The practicum is considered as the filling of the teacher education, aiming to apply in real context all the knowledge, both theoretical and practical. It is through a supervised professional practice that the pre-service teachers, in the accomplishment of the different tasks assigned to them, simultaneously with the experience in the practical context, develops professional competences of the teaching career, promoting a critical and reflexive spirit (about their practices). This document intends to understand the course during a school year, calling for reflection on the aspects of school life, the decisions taken and their results, as well as a reflection on reflection in action. This report is organized in five chapters: the first, "Introduction", where the document is contextualized; the second, "Personal Framing", referring to my personal and academic background, showing how it guided me and led me to the choose this profession; the third chapter, "Institutional Framework", where I refer to the context in which the practicum took place, taking into account the legal and regulatory levels in force, the trainee nucleus, the resident and shared classes assigned, the cooperating teacher and the faculty tutor; The fourth chapter, "Operational Framework", subdivided into three areas of performance, where a reflection on the process from the problems and difficulties to the strategies used to overcome them is carried out. Area 1, "Organization and Management of Teaching and Learning", corresponding to the design, planning, implementation and evaluation of teaching; Area 2, "School Participation and Community Relations" and area 3, "Professional Development", which includes the research study related to the strategies developed for the optimization of class time management. Last, the fifth chapter, "Conclusion", which includes final considerations and future perspectives, highlighting the importance of initial training and the preparation of the Internship Report as a reflexive practice.